2008
DOI: 10.1524/zkri.2008.0012
|View full text |Cite
|
Sign up to set email alerts
|

The P21/mC2/m phase transition in amphiboles: new data on synthetic Na(NaMg)Mg5Si8O22F2 and the role of differential polyhedral expansion

Abstract: The P2 1 /m $ C2/m displacive phase transition has been studied on a synthetic amphibole with unit formula A Na 0.90 B (Na 0.92 Mg 1.08 ) C (Mg 4.98 V 0.02 ) T Si 8 O 22 O3 F 2 . The evolution of the unit-cell parameters and of the intensities of a set of super-lattice reflections was monitored in the T range 100-944 K. Polynomial fitting of a 24 Landau potential to the evolution of the order parameter with T yielded a critical temperature (T c ) of 395 AE 5 K (398 AE 6 when considering low-T saturation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is now well-established that clinopyroxene undergoes a rapid reversible and nonquenchable displacive phase transition in which the P2 1 /c polymorph transforms to a high-T C2/c form ("HT-C2/c") at room-P and a high-P C2/c form ("HP-C2/c") at or below room-T Cámara et al (2007); 12 Iezzi et al (2007) kanoite). The two C-centered polymorphs have very different structures: the HT-C2/c phase has a fully-extended chain of tetrahedra, whereas the HP-C2/c phase has a strongly kinked chain.…”
Section: Comparisons With the P2 1 /C ↔ C2/c Transitions In Pyroxenesmentioning
confidence: 99%
“…It is now well-established that clinopyroxene undergoes a rapid reversible and nonquenchable displacive phase transition in which the P2 1 /c polymorph transforms to a high-T C2/c form ("HT-C2/c") at room-P and a high-P C2/c form ("HP-C2/c") at or below room-T Cámara et al (2007); 12 Iezzi et al (2007) kanoite). The two C-centered polymorphs have very different structures: the HT-C2/c phase has a fully-extended chain of tetrahedra, whereas the HP-C2/c phase has a strongly kinked chain.…”
Section: Comparisons With the P2 1 /C ↔ C2/c Transitions In Pyroxenesmentioning
confidence: 99%
“…A series of in-situ experiments have been performed on the low and high thermal behavior of amphiboles, on the basis of several experimental techniques (e.g., Sueno et al 1978;Cameron et al 1983;Cámara et al 2003Cámara et al , 2007Iezzi et al 2005a;Jenkins and Corona 2006), reviewed by Welch et al (2007). Some more recent studies are, e.g., those of Tribaudino et al (2008), Welch et al (2008) and Iezzi et al (2011) on richterite, Welch et al (2011b) on anthophyllite and Zema et al (2012) on gedrite.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature, the P2 1 /m phase occurs in the Mg-richer portion of the cummingtonite-grunerite join (Hirshmann et al 1994;Yang and Prewitt 2000;Boffa-Ballaran et al 2004). Recent works have also shown that synthetic "magnesiorichterite" [MRIC: Na(NaMg)Mg 5 Si 8 O 22 (OH) 2 ] and amphiboles along the join Na(NaMg)Mg 5 Si 8 O 22 (OH) 2 -Na(LiMg)Mg 5 Si 8 O 22 (OH) 2 have P2 1 /m symmetry (Iezzi et al 2004(Iezzi et al , 2006aCámara et al 2008).…”
Section: Introductionmentioning
confidence: 99%